Investigating the Effect of Lymnaea auricularia (snail) Powder on Different Species of Pathogenic Bacteria (Medico Legal Update, 2020)
The aim of this study was to investigate the antibacterial activity of Lymnaea auricularia (snail) tissuepowder and shell powder against different human pathogenic bacteria (Escherichia Coli, Pseudomonas aeruginoa and Klebsiella pneumonia). Four concentration was tested (75,100.125,150) mg\ml of the powderwith well diffusion assay. The highest activity of shell powder was in E. Coli at 75mg\ml concentration(19mm)inhibition zone, while the highest activity of tissue powder was in P. aeruginoa at 150mg\ml concentrationwith inhibition zone (28 mm). The powder extracts ‘ antimicrobial activity reveals that they may havebiologically active metabolites.